Pendampingan UMKM Frozen Melalui Sistem Penjualan Konsinyasi Guna Meningkatkan Potensi Penjualan dan Pembayaran - Sunani, Avi; Wahyu Indah Kirana, Nanda; Widodo, Condro; Lukitasari, Ika Chandra; Permatasari, Lintang Putri (Pendidikan Sejarah FKIP Universitas JAMBI, 2023)
The problem of partner SMEs frozen, in the home industry Rungkut, Surabaya, East Java, is that there are no structured consignment sales reports that are in accordance with accounting standards. In order to help solve the problem, the planned activity that will be carried out is to provide assistance to the partners of the SMEs frozen, in the home industry Rungkut, by increasing consignment sales report preparation capabilities. The implementation of this community service program uses the method of mentoring, discussion, and feedback to partners. The final result to be achieved in this community service activity is the existence of the ability of SMEs to prepare and apply a system-based consignment sales report using Microsoft word. Based on the activities we have carried out both offline and online, it could be concluded that the partners have periodically applied consignment sales report both manually and systemically. Other output from this activity is publications in the National Journal.